Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2481413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the display angle in museums on user's cognition, behavior, and subjective responses

Abstract: In order to achieve the intended level of communication with visitors in museums where large displays are installed, it is essential to understand how various display factors affect visitors. We explore the effects of the display angle on individual users. In our experiment, we set up three types of flat displays-vertical, horizontal, and tilted-and comprehensively tested users' cognitive, behavioral, and subjective aspects. The results showed that a significant difference could be discerned in regards to cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Users were more likely to perform two-handed, multi-touch gestures on the touch wall than on the touch table. Our study expands prior work observing gesture interactions of museum visitors [8,[24][25][26][27]29,32] to compare two touch platforms and to use unobtrusive methods to collect gesture interaction data. Based on our analysis, we present design implications for gestural interaction on large touchscreen displays, especially in public settings.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Users were more likely to perform two-handed, multi-touch gestures on the touch wall than on the touch table. Our study expands prior work observing gesture interactions of museum visitors [8,[24][25][26][27]29,32] to compare two touch platforms and to use unobtrusive methods to collect gesture interaction data. Based on our analysis, we present design implications for gestural interaction on large touchscreen displays, especially in public settings.…”
Section: Resultsmentioning
confidence: 78%
“…Previous work on general touchscreen interactions with single users and users in groups has provided many design considerations to improve usability. Ichino et al [29] performed a controlled laboratory exhibit to compare user responses to different display angles in museums; users rated tilted displays as superior in attracting attention and ease of use and interaction. Rogers et al [43] reported from a user study that a horizontal display resulted in members switching roles more often and having a greater awareness of the other group members, while the vertical display hindered collaboration.…”
Section: Interactive Tabletops and Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…They report on a variety of factors influenced by the configuration, e. g. participants noted different ergonomic issues between vertical and horizontal displays. Ichino et al [72] investigated the influence of display configuration in a museum context and found that tilted displays increased user experience (e. g. attracted attention and increased understanding of content). Forlines et al [46] showed that both display configuration and group size influence the performance for visual search tasks.…”
Section: Display Configurationmentioning
confidence: 99%
“…Past research has also explored how display angle affects a range of different aspects of usersÕ interaction with large interactive displays (e.g. [8,9]). However, relatively little attention has been paid to the impact that display angle has on usersÕ physiology over time and consequential musculoskeletal damage.…”
Section: Introductionmentioning
confidence: 99%